2015
DOI: 10.1002/ldr.2409
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Soil Chemical Properties Induced by Continuous Rice Cultivation: A Study on the Arid Nile Delta Soils of Egypt

Abstract: Changes in soil chemical properties resulting from continuous rice (Oryza sativa) cultivation on the Nile Delta soils of Egypt were examined. The eight soil profiles characterized for this study were designated as 0 (crop rotation without rice), 1 (crop rotation with rice after every 2 years), and 2, 3, 4, 5, 6, and 7 representing continuous rice cultivation for 2, 4, 8, 12, 15, and 20 years, respectively. Sampling was conducted at 0-20, 20-40, 40-60, and 60-80 cm depths for each profile and samples analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“… Country ( Table 8 ) Reference Tanzania Kashenge-Killenga et al (2016) : South-west, both salinity and sodicity, consistent with HWSD. No study found on salinity or sodicity in the north-west (Mwanza, Shinyanga) Egypt Delta: ( El-Shahway et al, 2016 ; Kotb et al, 2000 ) consistent with HWSD Nigeria Two studies in areas with no salinity according to HWSD: ( Akinbile et al, 2016 ; Akpan et al, 2015 ). No studies in areas with high salinity problems for rice according to HWSD and crop maps.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… Country ( Table 8 ) Reference Tanzania Kashenge-Killenga et al (2016) : South-west, both salinity and sodicity, consistent with HWSD. No study found on salinity or sodicity in the north-west (Mwanza, Shinyanga) Egypt Delta: ( El-Shahway et al, 2016 ; Kotb et al, 2000 ) consistent with HWSD Nigeria Two studies in areas with no salinity according to HWSD: ( Akinbile et al, 2016 ; Akpan et al, 2015 ). No studies in areas with high salinity problems for rice according to HWSD and crop maps.…”
Section: Discussionmentioning
confidence: 95%
“…Apart from lacking data on dams, data were lacking on the magnitude of these phenomena. A third source of uncertainty on salinity is about the extent to which drainage systems are in place and functioning properly in irrigated systems and the extent to which farmers re-use increasingly saline drainage water ( El-Shahway et al, 2016 ; Kotb et al, 2000 ). Uncertainty on coastal water dynamics, dams and drainage water use causes considerable uncertainty about the estimate of the area potentially affected by salinity.…”
Section: Discussionmentioning
confidence: 99%
“…The results imply that soils with lower position of the cg could supply more plant available K for the growth of ryegrassan inference consistent with the general conclusions drawn by Barré et al (2007Barré et al ( , 2008 and Paola et al (2016) from similar results. Moreover, the relationship between cg position and cumulative K uptake by ryegrass after eight harvests is stronger than that after four harvests, because K uptake by the earlier crops was sourced partly from exchangeable K and partly from non-exchangeable K, and the decrease in exchangeable K due to its removal by the crop led to a switch to the non-exchangeable form following repeated crops on K-deficient soils (Tributh et al, 1987;Surapaneni et al, 2002;El-Shahway et al, 2016). The release of nonexchangeable K was accompanied by a decrease in the intensity of the illite peak and a slight expansion of interlayer space in the mica layers (Li et al, 2015b).…”
Section: Release Of Potassium From Soil Reserves and Its Uptake As Afmentioning
confidence: 99%
“…The knowledge of soil characteristics of wetlands represents a relevant tool to consider risks and vulnerabilities binding on these habitats (Zdruli, 2014), such as salinisation of adjacent land by intrusion of salt water or wind transportation of salt crystals and gypsum sands. Under such scenario of disturbance and/or degradation of wetlands and consequently adjacent lands, functions and ecosystem services would be affected, which has a negative impact on the economies and social well-being of local populations (Nabahungu & Visser, 2013;Alexander et al, 2015;El-Shahway et al, 2015).…”
Section: Implications For Managementmentioning
confidence: 99%